PENGARUH STRUKTUR MODAL, UKURAN PERUSAHAAN, LEVERAGE, DAN INVESMNET OPPORTUNITY SET (IOS) TERHADAP KUALITAS LABA - Teguh Erawati; Dewi Rahmawati (Progress: Jurnal Pendidikan, Akuntansi dan Keuangan, 2022)
Earnings quality is earnings that reflect the continuation of earnings in the future, which is determined by the accrual component and cash conditions that show the actual financial performance of the company. This study aims to prove the effect of capital structure, firm size, leverage and investment opportunity set (IOS) on earnings quality. The research method used is purposive sampling with a total sample of 58 companies listed on the Indonesia Stock Exchange (IDX). This research was conducted using secondary data with the year of observation, namely 2017-2020. The data is obtained from financial statements taken from www.idx.com. The data analysis method used is descriptive statistical test, classical assumption test and hypothesis testing. The results showed that capital structure, leverage and investment opportunity set (IOS) did not have a significant effect on earnings quality, while firm size had a significant effect on earnings quality.